2005
DOI: 10.1104/pp.105.063941
|View full text |Cite
|
Sign up to set email alerts
|

Sites and Regulation of Polyamine Catabolism in the Tobacco Plant. Correlations with Cell Division/Expansion, Cell Cycle Progression, and Vascular Development

Abstract: We previously gave a picture of the homeostatic characteristics of polyamine (PA) biosynthesis and conjugation in tobacco (Nicotiana tabacum) plant organs during development. In this work, we present the sites and regulation of PA catabolism related to cell division/expansion, cell cycle progression, and vascular development in the tobacco plant. Diamine oxidase (DAO), PA oxidase (PAO), peroxidases (POXs), and putrescine N-methyltransferase expressions follow temporally and spatially discrete patterns in shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 68 publications
3
67
0
9
Order By: Relevance
“…Another possible explanation for the lack of phenotype shown by A-ZmPAO plants could be the involvement of additional and/or alternative H 2 O 2 sources, such as apoplastic CuAOs, that could cooperate with PAOs in H 2 O 2 delivery during tobacco xylem tissue differentiation. Indeed the simultaneous presence of CuAO and PAO activity working at the same time in the same tissues has been previously reported in tobacco, where the two enzymes have been proposed to cooperate during physiological and stress response events, such as lignification of vascular tissues (Paschalidis and Roubelakis-Angelakis, 2005) and wound healing responses . Furthermore, the phenotype shown by the RNAi-SAMDC transgenic plants could be ascribable to the absence of some specific PA directly involved in xylem differentiation, and therefore unrelated to its catabolism to H 2 O 2 and/or to the PA/H 2 O 2 ratio, once more underlining the complexity of PA physiology.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Another possible explanation for the lack of phenotype shown by A-ZmPAO plants could be the involvement of additional and/or alternative H 2 O 2 sources, such as apoplastic CuAOs, that could cooperate with PAOs in H 2 O 2 delivery during tobacco xylem tissue differentiation. Indeed the simultaneous presence of CuAO and PAO activity working at the same time in the same tissues has been previously reported in tobacco, where the two enzymes have been proposed to cooperate during physiological and stress response events, such as lignification of vascular tissues (Paschalidis and Roubelakis-Angelakis, 2005) and wound healing responses . Furthermore, the phenotype shown by the RNAi-SAMDC transgenic plants could be ascribable to the absence of some specific PA directly involved in xylem differentiation, and therefore unrelated to its catabolism to H 2 O 2 and/or to the PA/H 2 O 2 ratio, once more underlining the complexity of PA physiology.…”
Section: Discussionmentioning
confidence: 54%
“…In xylem precursors, PAO mainly has a cytoplasmic localization and it was shown that as the cells mature, the enzyme will accumulate in the cell wall parallel to secondary wall deposition and developmental cell death (Cona et al, 2005). Development of vascular tissues is associated with cell cycle/endocycle progression and amine oxidase expression in tobacco (Paschalidis and Roubelakis-Angelakis, 2005). It has been proposed that these events are to be linked with the physiological need for the higher production of H 2 O 2 via amine oxidases in the secretion pathway (Cona et al, 2005) and in the apoplast to drive peroxidase-catalyzed cross linking of cell wall polysaccharides and proteins to complete cell wall maturation, to stimulate endoreduplication, and possibly to act as a signal triggering xylem precursor cell death (Cona et al, 2005;Paschalidis and Roubelakis-Angelakis, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous Put improved Indian mustard seedling growth by preventing lipid peroxidation and denaturation of macromolecules through the induction of antioxidative enzymes and the increase of glutathione and carotenoid under NaCl stress (Verma and Mishra, 2005). Conversely, polyamines may act as a mediator or secondary messenger to activate a vast genetic network with a potential to provide defense against biotic and abiotic stresses (Paschalidis and Roubelakis-Angelakis, 2005;Cona et al, 2006). It has been proved that a wide array of genes regulating transcription, translation, signal transduction, stress protein biosynthesis, ethylene biosynthesis and action, isoprenoid and flavonoid biosyntheses was activated by polyamines.…”
Section: Introductionmentioning
confidence: 99%